2013
DOI: 10.1900/rds.2013.10.27
|View full text |Cite
|
Sign up to set email alerts
|

Low Total Testosterone Levels are Associated With the Metabolic Syndrome in Elderly Men: The Role of Body Weight, Lipids, Insulin Resistance, and Inflammation; The Ikaria Study

Abstract: ■ Abstract BACKGROUND:The prevalence of the metabolic syndrome (MetS) increases with age. Among other changes, testosterone levels decline with age. The relationship between testosterone levels and MetS components in older subjects has not been clearly defined until today. OBJEC-TIVES: The aim of this work was to evaluate the relationship between total serum testosterone levels and MetS and its components. METHODS: The working sample consisted of 467 elderly individuals (mean age 75 ± 6 years old, n = 220 men)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…Testosterone regulates glucose tolerance and insulin resistance independently from MetS with sex differences because higher testosterone level has a protective effect in men while representing a high risk of type‐2diabetes in women . Low testosterone level correlated with reduced glucose tolerance and insulin activity, particularly in elderly men and is always correlated with type‐2 diabetes. Androgen deprivation, as observed in patients with prostate cancer, favourites the development of type‐2 diabetes because of diminished pancreatic β‐cell function .…”
Section: Androgens and Type‐2 Diabetesmentioning
confidence: 99%
“…Testosterone regulates glucose tolerance and insulin resistance independently from MetS with sex differences because higher testosterone level has a protective effect in men while representing a high risk of type‐2diabetes in women . Low testosterone level correlated with reduced glucose tolerance and insulin activity, particularly in elderly men and is always correlated with type‐2 diabetes. Androgen deprivation, as observed in patients with prostate cancer, favourites the development of type‐2 diabetes because of diminished pancreatic β‐cell function .…”
Section: Androgens and Type‐2 Diabetesmentioning
confidence: 99%
“…9 Further details about the methods used in the baseline evaluation of the Ikaria Study may be found elsewhere. 10 …”
Section: Electrocardiogram Measurements Designationmentioning
confidence: 99%
“…In men, the most widely reported relationship between MetS, T2DM, and testosterone deficiency is a link between low testosterone levels, obesity, and insulin resistance . What is not clearly known, however, is the mechanism or causality .…”
Section: Pathophysiology Of Androgen Deficiencymentioning
confidence: 99%
“…16 In men, the most widely reported relationship between MetS, T2DM, and testosterone deficiency is a link between low testosterone levels, obesity, and insulin resistance. 2,3,9,15,[17][18][19] What is not clearly known, however, is the mechanism or causality. 20 Studies have demonstrated that testosterone levels fall with age regardless of obesity, and SHBG levels increase with age, yielding less bioavailable testosterone.…”
Section: Pathophysiology Of Androgen Deficiencymentioning
confidence: 99%